ISLAMISASI ILMU DALAM KONTEKS PENDIDIKAN ISLAM KONTEMPORER DI INDONESIA - Laelatul Badriah; Ahmad Syamsul Arifin (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
Islam is very concerned about and highly respects science. Science is very complex to navigate human life, al attas upholds science that will have a positive impact on the development and world civilization. There is a term in the category of religious knowledge and general knowledge which was introduced by al Ghazali. So al attas, in this case, will provide new knowledge and insights of all knowledge that will be affected by changes and developments in world civilization. With the concept of Islamic thought, the science of al Attas is applied in the context of modern Islamic education in Indonesia, from basic education institutions to higher education institutions. Which states the concept of Islamization of science in an integrated manner in the concept of Islamic education from aspects of educational institutions, aspects of the curriculum, aspects of educators, and aspects of students. These four aspects are an attempt to implement the concept of Islamization of science in real human life with the concept of the theory of nature inherent in humans as caliph on earth.